From uncertainty to adjustment: the influence of the 2023 Israel–Hamas War on Latin American Stock Market Volatility - Melo-Vega-Angeles, Oscar (2025)
This article examines how the 2023 Israel–Hamas War, in the context of geopolitical risk, influenced the volatility of Latin American stock markets via transmission channels such as exchange rate fluctuations and oil price dynamics. Our main findings, derived using a Bayesian panel vector autoregression, suggest that, prior to the outbreak, an increase in the exchange rate and oil prices led to higher stock market volatility; however, after the outbreak, the exchange rate depreciation played a role in reducing volatility. This suggests that Latin American markets internalised the geopolitical shock as part of a broader adjustment process instead of a persistent external risk.